2020
DOI: 10.1111/flan.12489
|View full text |Cite
|
Sign up to set email alerts
|

Role of developing language attitudes in a study abroad context on adoption of dialectal pronunciations

Abstract: This study examines how language attitudes play a role in the adoption of dialectal variants in second language (L2) pronunciation in a study abroad context. Twenty‐four North American university students participating in a 6‐week program in Buenos Aires, Argentina, were administered pre and posttest questionnaires and a posttest oral production task to determine how different background and attitudinal variables relate to production of two Argentine dialectal sounds, lenited‐/s/ and assibilated pre‐palatal /ʃ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…For proficiency level (Table 1), students were grouped according to their course level (intermediate, advanced), with a distinction made among the advanced level 8 between L2-advanced and Heritage-advanced as previous studies found differences between advanced L2 and heritage speakers for /d/ (Amengual, 2019). Students were asked to self-rate 9 their Spanish level in a preprogram questionnaire (Schmidt, 2020): beginner (1), lower-intermediate (2), intermediate (3), high-intermediate (4), advanced (5), high-advanced (6), near-native (7), and native (8). The one heritage speaker in the intermediate course self-rated her Spanish in line with the other heritage speakers and was therefore placed into the Heritage-advanced group.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…For proficiency level (Table 1), students were grouped according to their course level (intermediate, advanced), with a distinction made among the advanced level 8 between L2-advanced and Heritage-advanced as previous studies found differences between advanced L2 and heritage speakers for /d/ (Amengual, 2019). Students were asked to self-rate 9 their Spanish level in a preprogram questionnaire (Schmidt, 2020): beginner (1), lower-intermediate (2), intermediate (3), high-intermediate (4), advanced (5), high-advanced (6), near-native (7), and native (8). The one heritage speaker in the intermediate course self-rated her Spanish in line with the other heritage speakers and was therefore placed into the Heritage-advanced group.…”
Section: Methodsmentioning
confidence: 99%
“…The low production of intervocalic /d/ elision furthers the notion that certain dialectspecific phones are more acquirable than others. Intervocalic /d/ elision is similar to French /l/ elision in third person singular pronouns (Howard et al, 2006;Kennedy Terry, 2017) and Spanish coda /s/ aspiration/elision (Linford et al, 2021;Schmidt, 2020) in which there is a grapheme-to-phone mismatch, thus less acquirable than a one-to-one grapheme-to-phone correspondence such as [ʒ]/[ʃ] for <y> and <ll> in Argentine Spanish (Hoffman-González, 2015;Pozzi & Bayley, 2020;Schmidt, 2020) or Cairene Arabic [g] for the Arabic character < ‫>ﺝ‬ (Raish, 2015). Moreover, the elision of intervocalic /d/ may be less salient than other dialectal features.…”
Section: Dialect-specific Phonesmentioning
confidence: 95%
See 3 more Smart Citations